Conceptions of students from a rural context about photosynthesis - Vega, Yobana Lucía; Torres, Nidia Yaneth; Pedreros, Elliana Yizeth (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Photosynthesis is one of the most controversial topics for students, on the one hand, because of their lack of understanding and, on the other hand, it is a subject on which they have the most difficulties. Therefore, this research aims to describe the conceptions about photosynthesis of 24 10th and 11th grade students from an educational institution in the municipality of Coper, in the rural context of the department of Boyacá, Colombia. It was conducted according to a qualitative approach, which allows us to comprehend how students in a rural context understand photosynthesis and what other concepts they would associate in their conceptions. A 30-question questionnaire was used. It was found that students have alternative ideas that often lead them to think that photosynthesis is a type of plant respiration. It also became evident that they do not fully recognize the necessary compounds for the process to occur. This makes it very difficult for them to understand concepts such as autotrophic nutrition, breathing, gas exchange and metabolic pathways.